Family Assessment Device Among Families with Stunted Children Under Five Years in Kadu Village, Tangerang - Evanny Indah Manurung; Martina Pakpahan; Catharina Guinda Diannita (Faculty of Nursing, Universitas Pelita Harapan, 2025)
Nutritional status serves as an important indicator of health development in infants and young children. Insufficient growth in height and weight during the toddler stage can lead to nutritional issues that negatively impact health and may cause delays in cognitive development. This study aimed to examine the relationship between family functioning and the growth of toddlers with stunting in Kadu Village, Tangerang. A correlational design with a cross-sectional approach was applied, involving 64 families with stunted children under five years old. Data were collected using the Family Assessment Device (FAD), which measures seven dimensions of family functioning: problem-solving, communication, roles, affective responsiveness, affective involvement, behavior control, and general functioning. The height and weight of toddlers were validated through health records and direct measurement. Statistical analysis revealed that the role factor had a significant negative correlation with both child height (p = 0.001; r = -0.395) and weight (p = 0.002; r = -0.379), while problem-solving showed a positive correlation with height (p = 0.03; r = 0.271). These findings indicate that parental roles and involvement in daily care strongly influence toddler growth. Roles and problem-solving are part of the family function. Strengthening family roles and problem-solving skills is essential to improving nutritional outcomes and preventing stunting.